Nitrification process in a nuclear wastewater with high load of nitrogen, uranium and organic matter under ORP controlled. - Venturini, M. (2021)
Fil: Venturini, M. Ministerio de Economía. Secretaría de Energía. Comisión Nacional de Energía Atómica. Laboratorio de Biominería y Biotecnología Ambiental; Argentina.